Towards the Identification and Characterization of Putative Adult Human Lens Epithelial Stem Cells - Pandi Saranya; Madhu Shekhar; Aravind Haripriya; Veerappan Muthukkaruppan; Chidambaranathan Gowri Priya (Cells, 2023)
The anterior lens epithelium has the ability to differentiate into lens fibres throughout its life. The present study aims to identify and functionally characterize the adult stem cells in the human lens epithelium. Whole mounts of lens epithelium from donor eyes (normal/cataract) were immunostained for SOX2, gap junction protein alpha 1 (GJA1), PAX6, α, β and γ-crystallins, followed by a confocal analysis. The functional property of adult stem cells was analysed by their sphere forming ability using cultured lens epithelial cells from different zones. Based on marker expression, the lens epithelium was divided into four zones: the central zone, characterized by a small population of PAX6+, GJA1−, β-crystallin− and γ-crystallin− cells; the germinative zone, characterized by PAX6+, GJA1+, β-crystallin− and γ-crystallin−; the transitional zone, characterized by PAX6+, GJA1+, β-crystallin+ and γ-crystallin−; and the equatorial zone, characterized by PAX6+/−, GJA1+, β-crystallin+, and γ-crystallin+ cells. The putative lens epithelial stem cells identified as SOX2+ and GJA1 membrane expression negative cells were located only in the central zone (1.89 ± 0.84%). Compared to the other zones, a significant percentage of spheres were identified in the central zone (1.68 ± 1.04%), consistent with the location of the putative adult lens epithelial stem cells. In the cataractous lens, an absence of SOX2 expression and a significant reduction in sphere forming ability (0.33 ± 0.11%) were observed in the central zone. The above findings confirmed the presence of putative stem cells in the central zone of the adult human lens epithelium and indicated their probable association with cataract development.